The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1159/000531428
|View full text |Cite
|
Sign up to set email alerts
|

Balance Control in Individuals with Hearing Impairment: A Systematic Review and Meta-Analysis

Hamed Zarei,
Ali Asghar Norasteh,
Lauren J Lieberman
et al.

Abstract: Comprehensive insights into balance control of individuals with hearing impairment are compared with individuals with hearing. Primary sources were obtained from 7 databases including PubMed, LILACS, SCOPUS, CINAHL, PEDro, CENTRAL, and Web of Science. The search period extended from inception until January 5, 2022. The systematic review included 24 studies and 27 trials, with a total of 2,148 participants. The meta-analysis showed a significant difference in the average balance control between individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(100 reference statements)
1
0
0
Order By: Relevance
“…Another interesting finding of this study is that the postural sway velocity of the children with SNHL increased as the assessments were carried out without visual cues, and when the width of the support base of these children's feet was reduced. These findings corroborate other studies that also observed that children with SNHL use the visual and somatosensory systems to compensate their vestibular and balance deficits [67,68], thus this highlights the importance of the visual and somatosensory systems for regulating postural control in childhood.…”
Section: Discussionsupporting
confidence: 91%
“…Another interesting finding of this study is that the postural sway velocity of the children with SNHL increased as the assessments were carried out without visual cues, and when the width of the support base of these children's feet was reduced. These findings corroborate other studies that also observed that children with SNHL use the visual and somatosensory systems to compensate their vestibular and balance deficits [67,68], thus this highlights the importance of the visual and somatosensory systems for regulating postural control in childhood.…”
Section: Discussionsupporting
confidence: 91%